A joint exploration of executive subcomponents in binge drinking. (2nd November 2019) - Lannoy, Séverine; Dormal, Valérie; Billieux, Joël; Maurage, Pierre
Abstract: Background: Executive deficits have widely been reported in young binge drinkers over the last decade, but uncertainty remains regarding the specificity of these deficits and their variation across executive subcomponents. The current study aimed to offer a theoretically grounded and specific exploration of the differential deficits observed across executive functions in binge drinkers. Method: A total of 40 university students (20 binge drinkers: 10 women; 20 matched controls: 12 women) performed three validated neuropsychological tasks, each exploring a specific executive function, namely, shifting, updating, and inhibition (specifically resistance to distractor interference). Tasks were presented to participants in pseudo-randomized order. Repeated measure analyses of variance were performed to compare group performance. Results: A dissociation was observed across executive tasks regarding group differences: compared with controls, binge drinkers demonstrated preserved performance for shifting and updating abilities, but impaired inhibition. These results support the central role of inhibitory control in excessive alcohol consumption. In contrast to severe alcohol use disorders, binge drinking does not appear to be related to a general executive deficit. Conclusions: In view of the pivotal role played by inhibition impairments in the emergence of severe alcohol use disorders, these findings suggest that individualized evaluation and rehabilitation programs focusing on this inhibitory control subcomponent may improve control abilities in early stages of alcohol-related disorders.